Penyuluhan Keluarga Cerminan Masyarakat (Cemara): Peran Ketahanan Keluarga dalam Pembangunan Desa - Azizah, Wafiq Nur; Baharudin, Yusuf Hasan; Winandika, Gigih; Umayah, Urip; Musyarofah, Idarotul (Universitas Sebelas Maret, 2025)
This study involved 44 participants, including PKK women, Fattayat, and members of IPNU – IPPNU. The study used a quantitative design with a quasi-experimental approach (pre-test-post-test). The research procedure began with: 1) Preparation, 2) Pretest, 3) Intervention (pine counseling), 4) Posttest. This study identified the purpose and objectives of conducting this counseling, which was to provide understanding and insight to the participants regarding their readiness to face marriage and family life. Readiness to face marriage includes many aspects, among others: readiness to choose a life partner, physical readiness, psychological readiness, sociocultural readiness, academic readiness, financial readiness, readiness to live alongside a partner, readiness to start family life, readiness to care for children, and readiness to manage the household. In Glempangpasir village, internal family conflicts, the impact of the economic crisis, and weak communication among family members remain major challenges. The presence of this counseling is expected to strengthen family resilience and encourage mutual cooperation in building the village. Based on the above points, the author took the initiative to conduct counseling on readiness to face marriage. This counseling aims to provide information and education about readiness for marriage. It is intended to reduce or even eliminate obstacles or doubts that have become barriers to taking the step towards marriage, so that marriage is seen as a positive matter because, besides being an act of worship that completes half of the religion, it is also a means to continue the family lineage. This counseling was conducted through the collaboration between lecturers from the FKIP environment at UNUGHA and students from Nahdlatul Ulama University Al Ghazali Cilacap who were participating in community service activities. The counseling took place in one day and was attended by various community groups, including the village head, PKK women, Fattayat, IPNU – IPPNU members. The counseling material was based on data and delivered in an easily understandable way for various social groups in the local village. This training is expected to add knowledge and insight regarding how to face various aspects of marriage.Penelitian ini melibatkan 44 orang baik Ibu – Ibu PKK, Fattayat, IPNU – IPPNU. Penelitian ini menggunakan desain kuantitatif dengan pendekatan quasi-eksperimental (pre-test-post-test). Untuk prosedur penelitian, dimulai dari 1). Persiapan, 2). Pretest, 3). Intervensi (penyuluhan cemara, 4) Posttes. Penelitian ini mengidentifikasi Maksud dan tujuan diselenggarakannya penyuluhan ini untuk memberikan pemahaman dan wawasan kepada peserta penyuluhan terkait kesiapan diri menghadapi pernikahan dan berkeluarga. Kesiapan diri menghadapi pernikahan meliputi banyak hal, diantaranya : kesiapan diri memilih pasangan hidup, kesiapan fisik, kesiapan secara psikologis, kesiapan sosiokultural, kesiapan keilmuan, kesiapan finansial, kesiapan hidup berdampingan dengan pasangan, kesiapan memulai hidup berkeluarga, kesiapan merawat anak dan kesiapan diri mengelola rumah tangga. Di desa glempangpasir, konflik internal keluarga, dampak krisis ekonomi, serta lemahnya komunikasi antar keluarga masih menjadi tatangan utama. Adanya penyuluhan ini diharapkan mampu untuk memperkuat ketahanan keluarga serta dapat saling bergotong royong dalam membangun desa. Berangkat dari beberapa hal diatas, penulis berinisiatif mengadakan penyuluhan kesiapan diri menghadapi pernikahan. Penyuluhan ini dilakukan untuk memberikan informasi sekaligus edukasi terkait kesiapan meghadapi pernikahan. Agar hal-hal yang selama ini menjadi ganjalan atau keraguan untuk melangkah ke jenjang pernikahan menjadi berkurang atau bahkan hilang sehingga menikah itu merupakan suatu hal yang baik karena selain ibadah menyempurnakan separuh agama juga sebagai sarana meneruskan keturunan keluarga. Penyuluhan ini diselengarakan berkat kerjasama Dosen di lingkungan FKIP UNUGHA dengan mahasiswa Universitas Nahdlatul Ulama Al Ghazali Cilacap yang sedang menjalani kegiatan Kuliah Kerja Nyata. Penyuluhan ini diselenggaran dalam satu hari dan diharidi oleh berbagai lapisan masyarakat diantaranya Kepala Desa, Ibu – Ibu PKK, Fattayat, IPNU – IPPNU, materi penyuluhan yang digunakan berdasarkan data dan disampaikan dengan materi yang mudah dipahami oleh berbagai lapisan masyarakat desa setempat. Pelatihan ini diharapkan dapat menjadi tambahan wawasan ilmu terkait menyikapi berbagai hal yang ada pada pernikahan.